MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) EMPOWERMENT THROUGH QUADRUPLEHELIX APPROACH (A STUDY AT DEPARTMENT OF MICRO ENTERPRISE COOPERATIVES AND TRADE IN BATU CITY) - Lely Indah Mindarti; Ajie Hanif Muzaqi (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2018)
According to Local Regulation of Batu Number 1, 2016 about MSMEs empowerment and development, it is stated that MSMEs in Batu are able to become an alternative solution of the economic gap problems, such as unemployment and poverty. Through the concept of Quadruple helix model, the government along with private institutions, academics, and civil society contribute in implementing MSMEs empowerment as an effort to create economic development and equalization in Batu.The type of this research is descriptive research with qualitative approach. In collecting data, the researchers used observation technique, documentation, and interview toward the informants with criteria that they had to know, understand, and get involved in the implementation of MSMEs empowerment in Batu.The result of this research shows that the government of Batu through Department of Micro Enterprise Cooperatives and Trade of Batu implements MSMEs empowerment by relying on 4 main factors of empowerment, they are: financial capital access, human resource, partnership, and market strengthening. The government of Batu through Department of Micro Enterprise Cooperatives and Trade also established Integrated Business Service Centre (IBSC) as one of the commitments in empowering MSMEs and also making Batu as MSMEs centre. Based on the analysis result using the concept of Quadruple helix model, it is found that MSMEs empowerment in Batu involves collaboration of different sectors, they are: the government of Batu, private/business institutions, academics, and civil society through communities, groups, and non-governmental organizations.Based on the result of this research, it can be concluded that the government of Batu plays dominant roles in the interaction synergies of different sectors and being responsible in equitable economic development. Private institutions play roles as production developer, academics play roles as knowledge and skill development transferor and civil society plays roles as creative economic agents and product users.